The morphogenesis of higher education leadership: a social realist exploratory journey - Andrews, Ruth (Rhodes University, Faculty of Education, Department of Education)
The purpose of the study underpinning this thesis was to explore the tensions experienced by university leaders as they balance politics, power and the academic project whilst pursuing their ultimate concerns in the world. Universities are undergoing constant change, particularly in the present time of hypercomplexity, where the discourses of globalisation and neoliberalism condition higher education institutions and their leaders. This predisposes universities to operate as a market economy rather than as a public good. University leaders are under immense pressure as they seek to reposition themselves and exercise their agency in steering their institutions in a landscape fraught with complexity and contestation about the very nature of the modern university. The study was located in a traditional university in South Africa, which added another layer of complexity given the history of Apartheid and, the use of education as a means of discriminating against the black majority population, and the subsequent attempts by the government to transform the system following the first democratic election of 1994. Bhaskar's (1989) critical realism and Archer's (1998, 2000) social realism were used to frame the study theoretically. Bhaskar argues for the understanding of the world as an 'open system' in which experiences and events emerge from the tendential interplay of mechanisms at a layer of reality not directly accessible to empirical observation. Archer's (2000) social realism draws on critical realism to provide a set of tools that allows an exploration of the social world in more detail. This study draws on the tools of analytical dualism, or the temporary separation of structure, culture and agency for analytical purposes, and Archer's (1998) morphogenetic framework, which allows for the exploration of change, or non-change, over time. The overarching goal of the study was to explore how leaders at one South African university were enabled and constrained as they exercised their agency in the pursuit of projects they had identified to address their ultimate concerns about the world more generally and higher education in particular. However, the study also sought to explore the construct of leadership itself in a specific context by using Archer's (2007, 2012) theoretical work on reflexivity. The study drew on in-depth interviews with senior leaders at the institution, including two vice-chancellors. The interviews were subjected to analysis, and the inferential tools of abduction and retroduction were used to identify the interplay of mechanisms located at the level of the Real, the deepest layer of reality posited by Bhaskar (1978), which led to the events and experiences reported by leaders. A literature review was used to identify additional theories that were used in the processes of abduction and retroduction. The study revealed that change, or rather non-change, is often concealed in cultural rhetoric veiled in leadership practices in acts assimilating past ideology and codified rules and practices with new codified rules and practices. Leaders often draw on powerful relational networks as they reflexively exercise their agency, and these networks can also work to constrain change.
Keywords: Educational leadership -- South Africa; Education, Higher -- South Africa; Critical realism; Social realism; Educational change -- South Africa; Transformational leadership